Evaluation of the Ohmann Scoring System in the Diagnosis of Acute Appendicitis in Al-Yarmouk Teaching Hospital - Zaid Ghanim Saleem; Hayder S. Alkawaz (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Acute appendicitis is the most common abdominal surgical emergency requiring surgical intervention and its lifetime cumulative incidence is 7%. Yet its diagnosis is still sometimes confusing especially in young women and the elderly, which led to the introduction of various scoring systems, including the Ohmann score, aiming to increase efficiency in making the diagnosis and reduce negative appendectomies.Aim of Study: To evaluate the statistical parameters of the Ohmann scoring system in the diagnosis of acute appendicitis.Patients and Method: A prospective study of one year duration for patients carried in the emergency department of Al-Yarmouk Hospital on whom the decision of appendectomy was based on clinical evaluation and investigations, application of the Ohmann score on these patients and statistical analysis was done to assess its validity in diagnosing acute appendicitis, and then a comparison was done with the modified Alvarado scoring system (MASS) which is the more used score in our department.Results: A total of 230 patients were studied, 54.3% of them were females and 45.7% were males. 203 patients had inflamed appendix while 27 patients had normal appendix by histopathology (11.7 % negative appendectomy rate). The sensitivity of the Ohmann score was found to be 70%. The specificity was 81%, positive predictive value (PPV) was 97%, and negative predictive value (NPV) was 27%. The diagnostic accuracy of the Ohmann score was 72%. Conclusion: The Ohmann score proved to be simple, easy to use and inexpensive. Although its sensitivity is relatively low compared to the MASS